Lack of Effect of Rezafungin on QT/QTc Interval in Healthy Subjects. Issue 4 (2nd December 2019) - Flanagan, Shawn; Goodman, Daniel B.; Jandourek, Alena; O'Reilly, Terry; Sandison, Taylor
Abstract: Rezafungin is a new echinocandin in development for treatment of candidemia and invasive candidiasis, and for prophylaxis of invasive fungal infections. Rezafungin is the first echinocandin to undergo definitive QT/QTc study. This phase 1, single‐center, randomized, double‐blind trial was conducted to assess effects of intravenous rezafungin vs intravenous placebo (with moxifloxacin as positive control) on the QT interval of the electrocardiogram, corrected for heart rate by Fridericia's formula (QTcF), in healthy adults. Therapeutic (600 mg) and supratherapeutic (1400 mg) rezafungin doses were selected to achieve exposures 2.5‐fold higher than produced by the highest dose used in a phase 2 trial (400 mg once weekly). The primary end point was change in QTcF from baseline (ΔQTcF) as a function of plasma concentration, assessed by comparing upper bounds of the 2‐sided 90% confidence interval. The estimated mean ΔΔQTcF at the mean plasma concentrations for the rezafungin doses had upper bounds <10 milliseconds, within the upper bound of the 2‐sided 90% confidence interval. Intravenous rezafungin up to 1400 mg in a single dose did not prolong QT interval and had no apparent effect on repolarization or QRS duration. Electrocardiogram results showed no clinically significant effects of concern. These findings support the continued development of rezafungin.